Does the Introduction of N2-Fixing Trees in Forest Plantations on Tropical Soils Ameliorate Low Fertility and Enhance Carbon Sequestration via Interactions Between Biota and Nutrient Availability? Case Studies From Central Africa and South America - Koutika, Lydie-Stella; Zagatto, Maurício Rumenos Guidetti; Pereira, Arthur Prudêncio de Araujo; Miyittah, Michael; Tabacchioni, Silvia; Bevivino, Annamaria; Rumpel, Cornelia (Frontiers in Soil Science, 2021)
Plant and/or crop growth rely on nutrient dynamics driven by specific soil biota in different environments. This mini-review aims to provide an overview of interactions between soil organisms, nutrient dynamics, and C sequestration. To this end, we investigated published results from three forest plantations (eucalyptus monocultures and mixed plantations with N2-fixing acacia) on tropical nutrient-poor soils. One case study is located in Central Africa (Congolese coastal plains) and two others in South America (Southeastern Brazil). Overall, the studies showed that soil biota activity exerted positive effects on (i) C accretion, as both soil carbon and belowground and aboveground biomass are driven and enhanced by soil biota; and (ii) on nutrient dynamics and biogeochemical cycles in nutrient-poor soil of tropical ecosystems, which are boosted following C accumulation. On the other hand, the pedoclimatic environment may potentially impact soil functioning of mixed-species plantations through its influence on the composition and activity of bacterial communities. Regardless of the potential risk of acacia invasiveness, benefits such as pulp, fuelwood, electric pole and non-timber products supply, have been reported in Central Africa. We, therefore, conclude that including N2 fixing trees in forestry plantations as reported in this mini-review helps strengthen the links between soil biota, nutrient and SOC dynamics in mixed-species plantations on tropical nutrient-poor soils.